Children’s Mathematics and Verbal Self-concepts and Externalizing Behaviors: The Moderating Role of Peer Rejection at School - Passiatore, Ylenia; Grimaldi Capitello, Teresa; De Stasio, Simona; Millioni, Michela; Gentile, Simonetta; Fiorilli, Caterina (Frontiers in Psychology, 2017)
Previous research has found a strong correlation between children's academic self concept and their behavioral problems. The present study examined whether children’s peer rejection moderated the relationship between children's math and verbal self-concepts and their behavioral problems at school. We expected that children's social competence, as measured by peer rejection, moderated the negative effect of low self-concept on children's externalizing behaviors. Participants were 173 children (males=93, Mage=10.31 yrs, SD=1.43). The main findings showed that peer rejection moderated the effect of both low verbal and math self-concepts on children’s externalizing behavior. The results are discussed in terms of the protective factor played by children's social competence reducing the impact of low self-concept on children’s externalizing behaviors.